2016
DOI: 10.1007/s10900-016-0274-7
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Barriers and Utilization Among Adolescents and Young Adults Accessing Services for Homeless and Runaway Youth

Abstract: Homeless and runaway youth are at disproportionate risk for adverse health outcomes. Many barriers to accessing healthcare have been documented; however, the relative impact of discrete barriers on homeless youth healthcare utilization behavior is not firmly established. We administered a survey examining reported barriers and healthcare utilization among adolescents and young adults accessing services at three community centers for homeless and runaway youth. Of 180 respondents, 57 % were male, 80 % non-White… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
2
17
0
2
Order By: Relevance
“…fear, embarrassment, shame, self‐consciousness) barriers for young people 26 and several have found that their prevalence varies for different marginalised groups. Structural barriers have been reported more frequently than personal barriers for homeless young people 6 ; whereas, attitudinal barriers were more important for rural young people 7,27 . All three groups of barriers – structural, attitudinal and barriers relating to emerging autonomy – were described in earlier Australian research among young people 11 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…fear, embarrassment, shame, self‐consciousness) barriers for young people 26 and several have found that their prevalence varies for different marginalised groups. Structural barriers have been reported more frequently than personal barriers for homeless young people 6 ; whereas, attitudinal barriers were more important for rural young people 7,27 . All three groups of barriers – structural, attitudinal and barriers relating to emerging autonomy – were described in earlier Australian research among young people 11 .…”
Section: Discussionmentioning
confidence: 92%
“…However, these are exacerbated for certain marginalised young people. For example, structural barriers have been highlighted for homeless young people 6 and confidentiality concerns have been identified as a significant concern by rural young people 7 . Further, some marginalised groups of young people also experience barriers around language and culture, discrimination and stigmatisation 3 …”
mentioning
confidence: 99%
“…The experience of homelessness and mental illnesses, such as conduct disorders, anxiety disorders, and mood disorders, which are prevalent among homeless youth, may also contribute to or exacerbate health issues among this population [ 5 ]. Despite multiple health vulnerabilities, numerous barriers to accessing care exist, including inadequate transportation, cost, fear of judgment, and lack of trust [ 6 , 7 ]. Consequently, street-involved youth are often reluctant to engage with health services and frequently delay seeking help until their health problems deteriorate, which increases the risk of hospitalization [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…En complémentarité avec certains travaux qui montrent que les jeunes en situation de rue font une utilisation ciblée des services biomédicaux en santé sexuelle (Tyler et al, 2012), l'analyse des témoignages suggère que ce recours découle avant tout de leur perception des risques et des conséquences associés aux ITSS et aux grossesses non planifiées. À l'instar d'autres travaux, ce constat révèle que les jeunes en situation de rue ont tendance à utiliser les services dans une logique d'urgence (Barman-Ahikari et al, 2016 ;Stein et al, 2012) lorsqu'ils éprouvent de la peur à l'égard de leur santé (Chelvakumar et al, 2016) ou que leur état de santé s'est aggravé (Wenzel et al, 2001).…”
Section: Discussionunclassified
“…Ces jeunes ont d'ailleurs tendance à recourir aux services d'urgence plutôt qu'aux services de prévention (Barman-Ahikari et al, 2016 ;Stein et al, 2012). Chez les jeunes en situation de rue, le recours aux services est caractérisé notamment par le fait d'être une femme, d'être plus âgée, d'avoir été victime d'agression sexuelle et d'avoir peur pour sa santé (Chelvakumar et al, 2016 ;Klein et al, 2000 ;Tyler et al, 2012 ;Wenzel et al, 2001). À l'inverse, les jeunes en situation de rue d'origine ethnique minoritaire (Cochran et al, 2002) ou s'identifiant à la communauté LGBTQ (Tyler et al, 2012) utilisent moins les services qui leur sont offerts en raison de la stigmatisation et de la discrimination vécue à l'intérieur des organismes.…”
Section: Introductionunclassified